The Changes of House’s Spatial Caused by The User’s Religiosity in Pondok Indah Housing Estate Semarang - Annisa Dhia Zalva; Sumayya Ahida Fikri; Atiek Suprapti (Journal of Architectural Design and Urbanism, 2019)
Indonesia is a country with a majority Muslim population, which has been increasing its population every year. The increase in population is also accompanied by an increase in the need for residential houses. Residential houses that are now being developed are mostly located in a housing estate created by developers with the same physical form. This causes many phenomena to change the shape and spatial changes of the house due to the needs of different residents. One of those needs, is the need for religiosity to obey the teachings of religion. The example of places that experience the phenomenon of the change are Pondok Indah Housing Estate Semarang. Pondok Indah is a housing estate that has established for a long time and has undergone many changes in its houses. This research seeks to see how spatial changes occurs in Pondok Indah housing estate and how religiosity plays a role in these changes. Religiosity refers to the values of Muslim society based on the conception of Hablum Minallah, hablum minannas wa hablum minal ‘Alamien which means an islamic harmony of relations between humans and Allah, with each other, and with their natural environment. The retrieval of research data is done by interview and observation methods. In the changes in the spatial of houses in Pondok Indah Semarang housing estate there is an influence of religiosity on several aspects, including zoning, space, circulation, and spatial organization. These changes intentionally or not, have led to houses that are in accordance with the concepts of Islamic practice, namely Hablum Minallah, Hablum Minannas, and Hablum Minal ‘Alamin. The concept of Hablum Minallah's practice influences the changes in organizational and spatial aspects, Hablum Minannas influences the changes in zoning and spatial aspects, and Hablum Minal Alamin influences the change in aspects of circulation.